Financial Perfomance Analysis using The Economic Value Added (EVA) Method at PT. Bank Central Asia Tbk for the period 2021-2025 - Sarmilah Puspita; Melly Agustina Lastuti; Nayla Anindi Irawan; Zalfa Zahira Azzahra; Dion Julino; Riska Dwi Utari; Yossinomita Yossinomita (P3M Politeknik Negeri Ambon, 2026)
This study aims to analyze the financial performance of PT. Bank Central Asia Tbk during the 2021-2025 period using the Economic Value Added (EVA) method. Financial performance is generally measured using financial ratios: however, these indicators are often considered insufficient to reflect the company's actual condition and overall management performance. Therefore, an alternative approach such as EVA is necessary, as this method provides a more accurate measure of performance by assessing the economic value created by the company. This study employs a descriptive method with a qualitative approach. The data used consist of secondary data in the from of PT. Bank Central Asia Tbk's annual financial reports from 2021 to 2025, collected through documentation techniques. The analysis involves calculating and evaluating the EVA value for each year. The result of study indicates that PT. Bank Central Asia Tbk consistently recorded negative EVA (EVA<0) through the study period. This indicates that the company has not been able to generate economic value added, as the profits earned were not yet sufficient to cover its operational and capital cost. Therefore, it can be concluded that the financial performance of PT. Bank Central Asia Tbk during the 2021-2025 period, when measured using the EVA method, has not been optimal, although it shows an improving trend as the negative EVA values decreased year over year.